(untitled) (Raparin Journal of Humanities (RJH), 2024)
This paper investigated a critical feature of language contact phenomenon which is “grammatical loan translation”. In grammatical loan translation, the receptor language transfers a linguistic component whether it is morphology or syntax from the source language as simultaneously as the word order typology and grammatical features of that language. In other words, grammatical loan translation is interfererance of the grammatical rules and features of the source language to the receptor language, thus resulting in an unnatural change in the grammar of that language. Scholars in the field of language contact consider that grammatical loan translation is the resultant of the bilingual phenomenon. Additinaly, they believe that grammatical pattern translation rarely occurs without the existence of bilingual phenomenon in society. However, it is obvious that there is no bilingual phenomenon in Kurdistan Region as the Kurdish is the main language of education, media and governance, but many foreign (non-Kurdish) grammatical patterns came into the Kurdish language, especially into the language of news writing. This phenomenon reflected in all the categories of the language, and sentences. Grammatical loan translation has critical effect on language as it has been called language poison by researchers as well as language passive and language death by some others. Therefore, if language planning is not taken into consideration for this linguistic phenomenon, it can change the grammatical feature and gender of a language since the basic system of a language is preserved via grammar.